2001
DOI: 10.1046/j.1365-2222.2001.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in seasonal allergic rhinitis: influence of pollen season and therapy

Abstract: Exhaled nitric oxide (eNO) has been proposed as a potential indirect marker of lower airway inflammation in asthma. To investigate the existence of lower airways inflammation in allergic rhinitis eNO measurements were performed in 32 patients with symptomatic and asymptomatic seasonal allergic rhinitis early in and out of pollen seasons and in 80 healthy volunteers. To further define how exhaled NO is modified by therapy, NO levels were detected following 1-month treatment with either inhaled steroids or non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
49
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 29 publications
8
49
0
7
Order By: Relevance
“…Epithelial destruction, mast cell and eosinophil accumulation, T-Iymphocyte activation and enhanced cytokine expression are observed both in the nasal mucosa and in bronchial biopsies in asthma (2). In addition, the detection and measurement of non-invasive inflammatory markers strongly support the existence of lower airway inflammation in allergic rhinitis both in and out of allergen season (3)(4)(5). These observations support the view that there is a close link between allergic rhinitis and asthma and these diseases may represent distinct manifestations of a unique inflammatory process in the airways that leads to the concept of "one airway-one disease".…”
supporting
confidence: 56%
“…Epithelial destruction, mast cell and eosinophil accumulation, T-Iymphocyte activation and enhanced cytokine expression are observed both in the nasal mucosa and in bronchial biopsies in asthma (2). In addition, the detection and measurement of non-invasive inflammatory markers strongly support the existence of lower airway inflammation in allergic rhinitis both in and out of allergen season (3)(4)(5). These observations support the view that there is a close link between allergic rhinitis and asthma and these diseases may represent distinct manifestations of a unique inflammatory process in the airways that leads to the concept of "one airway-one disease".…”
supporting
confidence: 56%
“…However, our results are consistent with those of Berlyne et al [50] comparing eNO to induced sputum, and are in accordance with the hypothesis of a similar physiological process between atopic and non-atopic asthma. Furthermore, the eNO discrepancy between non-atopic asthma with rhinitis and non-atopic asthma without rhinitis could be due to a difference of frequency and intensity of stimulation to an unknown allergen [51]. An intermittent stimulus could act in non-atopic asthma without rhinitis, while in non-atopic asthma with rhinitis a more prolonged exposition during the year could result in more marked symptoms associated with asthma and rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…KEYWORDS: Allergy, bronchial asthma, latex, nitric oxide E xhaled nitric oxide (eNO) has been described as a marker of allergic airway inflammation in both rhinitic and asthmatic subjects [1][2][3][4][5][6][7]. eNO levels may be elevated in patients before asthmatic symptoms develop [8,9]. HENRIKSEN et al [8] and GRATZIOU et al…”
mentioning
confidence: 99%
“…eNO levels may be elevated in patients before asthmatic symptoms develop [8,9]. HENRIKSEN et al [8] and GRATZIOU et al[9] observed a seasonal rise in eNO levels in pollensensitised subjects with and without rhinitic and/or asthmatic symptoms, with a tendency towards increased concentrations in symptomatic subjects.Despite the considerable number of publications and results indicating relations between baseline eNO level and/or eNO changes on the one hand and symptoms [9][10][11], bronchial hyperresponsiveness [12,13] and inflammatory parameters of the airways [14] on the other, the clinical role of eNO measurements has not been exactly defined. Moreover, the relation between eNO levels and eNO changes following laboratory allergen challenge has so far rarely been compared between subjects with rhinitic and those with asthmatic responses.…”
mentioning
confidence: 99%